The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/mgg3.1985
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene sequencing of FYCO1 identified a novel mutation in a Pakistani family for autosomal recessive congenital cataract

Abstract: Background Congenital cataract is causing one‐third of blindness worldwide. Congenital cataract is heterogeneous in its inheritance patterns. The current study is aimed to explore the unknown genetic causes underlying congenital cataracts. Methods Blood samples from affected and normal individuals of n = 25 Pakistani families identified with congenital cataracts were collected. Genomic DNA was extracted and Sanger sequencing was performed to identify novel pathogenic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…This gene encodes a protein that contains 1478 amino acids and has a mass of 166.9k daltons. Functional protein analysis found four domains in FYCO1: RUN domain with 36–173 amino acid residues; coiled-coil domain carrying a sequence of 224–1154 residues; Znf domain comprising a sequence of 1166–1231 residues; and GOLD domain with a sequence of 1339–1466 residues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This gene encodes a protein that contains 1478 amino acids and has a mass of 166.9k daltons. Functional protein analysis found four domains in FYCO1: RUN domain with 36–173 amino acid residues; coiled-coil domain carrying a sequence of 224–1154 residues; Znf domain comprising a sequence of 1166–1231 residues; and GOLD domain with a sequence of 1339–1466 residues [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until the present, out of the total reported mutations detected in FYCO1 associated with CC, nineteen variants resulted in truncation of protein vulnerable with GOLD or coiled-coil protein domains [ 8 ]. In particular, an earlier study identified frameshift and nonsense mutation of FYCO1 associated CC in thirteen unrelated families [ 14 ]. Additionally, another report determining the disease linked genetic abnormalities in three consanguineous families investigated one previously known and two naïve nucleotide variants in the FYCO1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations